Distribution Law of Metro Stray Current in Red Soil Region - CHENG Hongbo; LU Weinan; XIE Zining; LIN Shan; WANG Fangling (Chengshi guidao jiaotong yanjiu)
[Objective] Due to the significant difference in soil characteristics compared to other types of soil, such as pH value, salinity, and soil resistivity, the red soil features more severe corrosion of metal facilities along metro lines caused by the stray current in its environment. Therefore, it is necessary to thoroughly analyze the distribution law of metro system stray current in red soil regions, exploring effective protection measures against stray current in such environments. [Method] The distribution law of current density and potential gradient of stray current in soil is analyzed. A simulation model of metro line stray current is established to analyze the transverse and longitudinal distribution law of metro stray current in red soil environments, as well as the associated potential gradient distribution. The red soil is compared with three typical types of soil (desert soil, alpine soil, and saline-alkali soil) and the differences in stray current distribution under various soil conditions are studied. The influence law and impact range of rail resistance, rail-to-earth resistance, and power supply voltage on the ground potential caused by stray current in red soil are also analyzed. [Result & Conclusion] In red soil environment, stray current gradually decreases from the centerline of metro line toward both sides, and after dissipation through the soil, a recovery phenomenon occurs near substations. Compared with the other three soil types, the stray current in red soil has a wider impact range. Measures such as reducing the longitudinal resistance of rails, increasing the rail-to-earth resistance, and raising the power supply voltage can effectively reduce the impact of stray current in red soil.